2016
DOI: 10.1097/j.pain.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of opioids for nonmalignant pain among community-dwelling persons with and without Alzheimer disease in Finland: a nationwide register-based study

Abstract: Persons with Alzheimer disease (AD) commonly present with chronic nonmalignant pain, but long-term use of opioids among this population has not been studied previously. Our aim was to investigate the prevalence of long-term (≥180 days) use of opioids for nonmalignant pain and associated factors among community-dwelling persons with AD and to compare the prevalence with a matched cohort without AD. The Medication use and Alzheimer's disease (MEDALZ) cohort was used for this study, comprising all community-dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 38 publications
5
55
0
Order By: Relevance
“…45,46 On the other hand, the lower prevalence of opioid use may indicate the clinical reality of the benefits of reducing sedative ADRs in vulnerable persons with AD. The prevalence and duration of concomitant BZDR and opioid use were higher among persons without AD than among those with AD, although BZDR use was more common in the AD group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…45,46 On the other hand, the lower prevalence of opioid use may indicate the clinical reality of the benefits of reducing sedative ADRs in vulnerable persons with AD. The prevalence and duration of concomitant BZDR and opioid use were higher among persons without AD than among those with AD, although BZDR use was more common in the AD group.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have revealed that individuals with AD or dementia are less likely to be prescribed analgesic medications than those without AD or dementia. 45,46 On the other hand, the lower prevalence of opioid use may indicate the clinical reality of the benefits of reducing sedative ADRs in vulnerable persons with AD. Specific reasons for this difference will require further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that pain in dementia is frequently treated with opioids [3,4]. Even long-term use of opioids is common in dementia, yet slightly less so than among older people generally [5,6]. However, older persons are more susceptible to opioid-related adverse drug effects and events (ADEs) [7,8].…”
Section: Introductionmentioning
confidence: 99%